The symphonic poem in Slovene music - Venišnik, Vesna (Muzikološki zbornik, 2013)
The article will outline the characteristics of Slovene symphonic poems through the programmes on which the composers referenced their symphonic poems and with musical analyses of selected works of the genre.
Keywords: simfonična glasba; simfonična pesnitev; slovenska glasba